Educação pelos ritos de iniciação: contribuição da tradição cultural ma-sena ao currículo formal das escolas de Moçambique - Braço, António Domingos (2008)
The goal of this Dissertation is to analyze Education in Mozambique in the view of the Ma-Sena ethnic rites of initiation concerning learning to be, learning to live together, learning to know, and learning to do in community; as well as the Ma-Sena s valuable contribution towards building-up socio-cultural identities in Mozambique. This paper also hopes to contribute to the development of a new Educational Curriculum, in which the local knowledge should be included. A qualitative survey was conducted in the Caia district (Sofala County, central region of Mozambique Republic), with local leaders (régulos), teachers, parents and learners. They were asked about the Ma-Sena rites of initiation, its importance in the community and the possibility of having them included in the regular educational curriculum. As per Clifford Geertz, Culture must be considered in the view of its cultural symbol s diversity . As Mozambique has a great range of cultural diversity, in which the national identity is basically build-up by exchanging different culture knowledge, we understand that a new school program based upon the dialogue with the local community - should be developed, having the Ma-Sena first rituals as its main part in order to reinforce and spread the cultural knowledge among the community. The importance of having such a change was reported by those who were interviewed. Aware of the ongoing cultural domain and the increasing lack of national values (even after the independence), the interviewed people are willing to rescue the local knowledge. We also realized that - as an educational practice - the Ma-Sena first rituals for a boy is an important step, once it works as a bridge on his adult life. The imposition of a new name, brings by itself, a new identity for him. The knowledge to be acquired and the actions to be adopted by him are of a great importance for his social-cultural identity; such as the revelation of the sacredness, sexuality and death. The survey also showed us that what is crucial for the educational curriculum, is not important for the ones who attend the school lessons. For the local people, the knowledge acquired through the Ma-Sena first rituals is really important, due to its unquestionable cultural values. Its lost would cause havoc throughout the community, and it might imply in the group extinction. As per these findings, we concluded that in order to represent the real Mozambican culture, the educational curriculum should be reorganized having as its basis the dialogue with the local people, and its cultural knowledge